Budget impact analysis of high-priced orphan medicinal products intended for the treatment of rare diseases in China: evidence from a densely populated metropolis of Chengdu - Xiaoxing Zhang; Tingting Zhou; Jing Zhou; Doudou Zhang; Yili Yang; Jay Pan (BMC, 2024)
Abstract Background An increasing number of orphan medicinal products (OMPs) are being included in social health insurance schemes, significantly improving access to medicines for patients with rare diseases. However, high-priced OMPs are still not covered, primarily due to health equity controversies and inadequate data systems required for economic evaluation. The aim of this study was to estimate the burden of drug expenditures and the size of the reimbursement budget required for high-priced OMPs from the perspectives of society and healthcare payers. Methods The study performed a budget impact analysis using data from multiple sources to estimate the reimbursement budget for high-priced OMPs in Chengdu, a densely populated metropolis in China. The budget analysis consisted of three main elements: the number of patients, the price of drugs, and the simulated policy scenario. By adjusting the combinations of these elements, the budget fluctuations for payers were estimated. Furthermore, the study predicted the budget trend for the next three years to validate its sustainability. Results The analysis indicated that 98 rare disease patients in Chengdu required high-priced OMPs in 2019. This suggested a projected budget of CNY 179 million for these patients without reimbursement policies, from a societal perspective. Under six assumed policy scenarios, this budget ranged from CNY 32 million to CNY 156 million. Over the next three years, the annual budget was estimated to range from CNY 200 million to CNY 1.303 billion. Conclusion Integration of multi-source data helps to obtain more scientifically reliable results on budget impacts. The study found that the budgetary impacts of high-priced OMPs on society and payers are relatively limited. Health policymakers can choose appropriate reimbursement strategies based on financial affordability among a diverse mix of elements. The results of related studies provided insights for optimizing the allocation of health resources and improving patient access to medications.